2017
DOI: 10.1080/10715762.2017.1412433
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin-labelling of the EutC subunit in B12-dependent ethanolamine ammonia-lyase reveals dynamics and a two-state conformational equilibrium in the N-terminal, signal-sequence-associated domain

Abstract: The B (adenosylcobalamin)-dependent ethanolamine ammonia-lyase (EAL) is a product of the ethanolamine utilisation (eut) gene cluster, that is involved in human gut microbiome homeostasis and in disease conditions caused by pathogenic strains of Salmonella and Escherichia coli. Toward elucidation of the molecular basis of EAL catalysis, and its intracellular trafficking and targeting to the Eut biomicrocompartment (BMC), we have applied electron spin-labelling and electron paramagnetic resonance spectroscopy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…NRs are used in the most of spin labelling applications due to their smaller size and less potential disturbance of the structure of labelled macromolecules. In this issue Nforneh et al [2] report on the EPR spin-labelling application of 4-maleimido-TEMPO nitroxide to elucidate the molecular basis of catalysis of B12-dependent ethanolamine ammonia-lyase. The EPR studies revealed dynamics and a two state conformational equilibrium in the N-terminal, signal sequence-associated domain.…”
mentioning
confidence: 99%
“…NRs are used in the most of spin labelling applications due to their smaller size and less potential disturbance of the structure of labelled macromolecules. In this issue Nforneh et al [2] report on the EPR spin-labelling application of 4-maleimido-TEMPO nitroxide to elucidate the molecular basis of catalysis of B12-dependent ethanolamine ammonia-lyase. The EPR studies revealed dynamics and a two state conformational equilibrium in the N-terminal, signal sequence-associated domain.…”
mentioning
confidence: 99%